Designing and Evaluating Collaborative Projects in Learning Communities: Innovative Practices and Strategies - Parahakaran, Suma (International Journal of Advanced Corporate Learning (iJAC), 2016)
Abstract The purpose of this review is to focus on the opportunities available for Corporates, Policy makers and Universities to strengthen ties which are mutually beneficial to all and to the economic growth of the Country. One of the main objectives is to explain how learning communities can be achieved by linking all the three sectors mentioned above so that they become the resource for the nation and has long term sustainable solutions as well as gaining grounds of goodwill from the public sectors. The blended learning programs existing in Universities can be expanded to join ventures with corporate companies to accommodate large learning platforms through peer to peer teaching and learning. This study introduces a model after a detailed review that links educational policies, Higher Institutions through Learning Communities and Corporates for sustainable human resource development. Past research conducted by the research team on e-platforms, revealed findings that there is a wide scope for collaborative projects integrated through e -learning that can contribute to enhance practical skills and gaining knowledge. Currently, the sharing of knowledge is limited and skewed towards academic excellence. At the same time, corporate companies are tight with budgets on areas that can be complemented through student interns. Peer to peer learning and research based learning can benefit both students and corporate companies through the establishment of joint projects. CSR taken up by corporates then stand to gain in the long term. This research review therefore concludes a new agenda, a new platform for nations to strengthen their economy and bring youth power to rebuild gaps that have become unsustainable. The model promises that links between corporate and educational ventures becomes mutually beneficial to each other, strengthens stakeholder capacity and gains the goodwill of the local communities. The results of the review will establish new grounds with new insights for Government and Policy makers to strengthen economy and upgrade education systems. Ethical and Context based Learning communities will become the crest jewel of any nation.